ChemInform Abstract: Rapid Synthesis of Fused Oxabicycles Through the Molecular Rearrangement of Spirocyclic Ethers. Issue 11 (18th March 2014) - Palmer, Leoni I.; Veits, Gesine K.; Read de Alaniz, Javier
Abstract 5, 5‐Spirocyclic cyclopentenones undergo Amberlyst‐15‐catalyzed ring opening/ring closure rearrangement to form tetrahydropyrans (II) and (IV).